2015
DOI: 10.1007/s00122-015-2588-8
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of flecking and its relationship to disease resistance in the IBM maize mapping population

Abstract: In this paper, we determine the genetic architecture controlling leaf flecking in maize and investigate its relationship to disease resistance and the defense response. Flecking is defined as a mild, often environmentally dependent lesion phenotype observed on the leaves of several commonly used maize inbred lines. Anecdotal evidence suggests a link between flecking and enhanced broad-spectrum disease resistance. Neither the genetic basis underlying flecking nor its possible relationship to disease resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…B), appearing in several widely used lines as well as in several other species such as barley (Makepeace et al , ), wheat (Nair and Tomar, ) and oats (Ferdinandsen and Winge, ). Recent work has indicated that in some cases flecking seems to be a mild form of misregulated HR (Olukolu et al , ; Vontimitta et al , ).…”
Section: Conceptsmentioning
confidence: 99%
“…B), appearing in several widely used lines as well as in several other species such as barley (Makepeace et al , ), wheat (Nair and Tomar, ) and oats (Ferdinandsen and Winge, ). Recent work has indicated that in some cases flecking seems to be a mild form of misregulated HR (Olukolu et al , ; Vontimitta et al , ).…”
Section: Conceptsmentioning
confidence: 99%
“…Despite its potential utility as a convenient marker for disease resistance, there have been few attempts to understand its genetic basis and its relationship to disease resistance. A recent study using 300 lines from the maize intermated B73 3 Mo17 advanced intercross line mapping population identified low but moderately significant positive correlations between increased flecking and increased disease resistance and defense response (Vontimitta et al, 2015). In this study, using much larger populations, we show that the genetic architecture controlling variation in the flecking phenotype is complex.…”
Section: Discussionmentioning
confidence: 49%
“…A recent study using 300 lines from the maize intermated B73 3 Mo17 population advanced intercross line mapping population identified low but moderately significant positive correlations between increased flecking and increased disease resistance and defense response (Vontimitta et al, 2015). Loci associated with variation in flecking were mapped, although these loci did not colocalize with QTLs identified previously for disease resistance and defense response traits (BalintKurti et al, 2007(BalintKurti et al, , 2008(BalintKurti et al, , 2010Olukolu et al, 2013).…”
mentioning
confidence: 87%
See 2 more Smart Citations